Adaptation of the Cambridge curriculum: A comparative study of public and Islamic schools - Ilma, Labibah Sayaka; Asrohah, Hanun; Zainiyati, Husniyatus Salamah (Curricula: Journal of Curriculum Development, 2025)
This research aims to explore how the Cambridge curriculum can be adapted as a relevant educational strategy for addressing global challenges, particularly in developing countries such as Indonesia. In the inequality between national education policy and its implementation in the field, the Cambridge curriculum offers an approach that emphasizes critical thinking, collaboration, and global-mindedness. The method used in this study is a qualitative literature review, analyzing various academic sources and reports on the implementation of the Cambridge curriculum in different school contexts. The results of the study show that the adaptation of the Cambridge curriculum in Indonesia, both in public and Islamic-based schools, exhibits different dynamics. However, both have a positive impact. Public schools implement this curriculum directly with a primary focus on global academic standards, without the need to conform to religious values. Meanwhile, the Islamic school has successfully combined the Cambridge curriculum with Islamic values, creating an educational model that is not only academically global but also spiritually and morally strong. Both approaches show great potential in bridging local education with global standards in a contextual and relevant manner. AbstrakPenelitian ini bertujuan untuk mengeksplorasi bagaimana adaptasi kurikulum Cambridge dapat menjadi strategi pendidikan yang relevan dalam menjawab tantangan global, khususnya bagi negara berkembang seperti Indonesia. Di tengah ketimpangan antara kebijakan pendidikan nasional dan pelaksanaannya di lapangan, kurikulum cambridge menawarkan pendekatan yang menekankan pada kemampuan berpikir kritis, kolaboratif, dan global-mindedness. Metode yang digunakan dalam penelitian ini adalah studi literatur kualitatif, dengan menganalisis berbagai sumber akademik dan laporan implementasi kurikulum cambridge di berbagai konteks sekolah. Hasil penelitian menunjukkan bahwa adaptasi kurikulum cambridge di Indonesia, baik di sekolah umum maupun berbasis Islam, menunjukkan dinamika yang berbeda namun keduanya berdampak positif. Sekolah umum menerapkan kurikulum ini secara langsung dengan fokus utama pada standar akademik global, tanpa perlu menyesuaikan dengan nilai-nilai keagamaan. Sementara itu, sekolah Islam berhasil menggabungkan kurikulum cambridge dengan nilai-nilai keislaman, menciptakan model pendidikan yang tidak hanya global secara akademik, tetapi juga kuat secara spiritual dan moral. Kedua pendekatan ini menunjukkan potensi besar dalam menjembatani pendidikan lokal dengan standar global secara kontekstual dan relevan.Kata Kunci: kurikulum Cambridge; sekolah Islam; sekolah negeri